Optimum salinity for growth of mangrove crab Scylla serrata seed in recirculation systems - Yuni Puji Hastuti; Ridwan Affandi; Mafatih Devi Safrina; Kurnia Faturrohman; Wildan Nurussalam (Jurnal Akuakultur Indonesia)
ABSTRACT